Prokalsitonin dan Sel Darah Putih sebagai Penanda Infeksi pada Anak dengan Ketoasidosis Diabetikum - Nur Rochmah; Muhammad Faizi; Yudhi Kurniawan; Latifatu Choirunisa; Anang Endaryanto; Soetjipto Soetjipto (Majalah Kedokteran Indonesia, 2020)
Introduction: Diabetic ketoacidosis (DKA), an acute complication of type 1 (insulin dependent) diabetes mellitus (T1DM), can be precipitated by infection. Procalcitonin (PCT) is an accurate marker of bacteremia, sepsis, and inflammation, however white blood cells (WBC) are still often used by clinicians. We aimed to analyze PCT levels and WBC counts in children with DKA.Methods: A cross-sectional study was conducted in Dr. Soetomo General Hospital, Surabaya, Indonesia, between 2015 and 2019. T1DM and DKA diagnosis was based on the International Society for Pediatric and Adolescent Diabetes. PCT levels and WBC counts were measured in samples from patients with and without DKA, and were compared using the Mann-Whitney test.Results: A total of 41 samples were included, with 15 samples (36.6%) from children with DKA, and 26 (63.4%) from children without DKA. PCT levels and WBC counts were significantly higher in those with DKA (p less than 0.001). The receiver operating characteristic curve analysis of WBC was lower than PCT (0.849 vs. 0.982). PCT had a higher sensitivity and spesificity as an infection marker than WBC (93.3 vs. 86.7; 92.3 vs. 88.5, respectively).Conclusion: PCT is a better infection marker in children with DKA than WBC